Vitamin C and Helicobacter pylori Infection: Current Knowledge and Future Prospects - Mei, Haixin; Tu, Hongbin (Frontiers in Physiology, 2018)
The gram-negative bacterium Helicobacter pylori (H. pylori) infection is predominantly known for its strong connection with development of gastric diseases, including gastritis, peptic ulcer disease and gastric cancer. Numerous clinical reports showed that ascorbic acid deficiency has been associated with gastritis, vitamin C levels both in gastric juice and serum have consistently been confirmed to be low in patients with H. pylori infected gastritis and peptic ulcers. Ascorbic acid supplementation was possibly related to decreased incidences of bleeding from peptic ulcer disease and gastric cancer. H. pylori eradication was shown to increase vitamin C levels, whilst the benefits of ascorbic acid oral intake to the effectiveness of H. pylori-eradication therapy are controversial. Recent studies suggest that ascorbate intake intravenously, but not orally, pharmacologic ascorbate concentrations of 25 ~ 30 mmol/L are easily and safely achieved in blood, several millimolar in tissues as well as in interstitial fluid. Pharmacologic ascorbate can exert local pro-oxidant effects as a drug by mediating hydrogen peroxide (H2O2) formation, which were applied to animal and clinical trials of cancer, sepsis, and severe burns etc. In this review, we summarize current knowledge of the associations of vitamin C and H. pylori infection, and outline some potential strategies for H. pylori intervention from emerging advances on ascorbic acid physiology and pharmacology.